Trends in cognitive outcomes in middle-aged Americans across three birth cohorts - Rebecca T. Brown; Xi Zuo; Corey T. McMillan; Shana D. Stites; Irma T. Elo; Kenneth M. Langa; Jason Karlawish; Dawei Xie (PLoS ONE, 2025)
Middle age is a key life course period for targeting modifiable risk factors for late-life cognitive decline. Although the prevalence of chronic conditions that are risk factors for cognitive impairment has increased in middle-aged adults since the 1990s, little is known about corresponding trends in cognitive trajectories and incidence of cognitive impairment. We conducted a cohort study of 7,852 participants ages 50–56 enrolled from 1998–2010 in the Health and Retirement Study (HRS) without cognitive impairment at baseline. Participants were followed biennially to examine cognitive trajectories and new-onset cognitive impairment by age 65, based on the HRS cognitive test battery. We used mixed effects models to examine change in cognitive scores and Cox regression models to compare incidence of cognitive impairment no dementia (CIND) across three birth cohorts (1942–1947, “War Babies”; 1948–1953, “Early Baby Boomers”; 1954–1959, “Mid Baby Boomers”). Mid Boomers had lower baseline cognitive scores compared to earlier cohorts but a slower rate of cognitive decline. Hazards of CIND were higher among White Early and Mid Boomers compared to War Babies in the first half of follow-up, but lower in the second half. In both trajectory and incidence analyses, those with lower educational attainment and racial/ethnic minorities were at higher risk for worse cognitive outcomes. Findings show mixed trends in cognitive outcomes among middle-aged Americans. Overall, Mid Boomers had lower baseline cognitive scores but slower decline compared to earlier cohorts. However, disparities in cognitive outcomes persisted among those with lower educational attainment and racial/ethnic minorities.